Biomechanics and Mechanism of Action of Indirect Lumbar Decompression and the Evolution of a Stand-alone Spinous Process Spacer. Issue 2 (6th December 2019) - Falowski, Steven M; Sayed, Dawood; Deer, Timothy R; Brescacin, Dane; Liang, Kevin
Abstract: Objective: Objective Interspinous process spacers are used in the treatment of lumbar spinal stenosis by preventing extension at the implanted level and reducing claudication, which is a common symptom of lumbar spinal stenosis. This review assessed the current safety and performance of lumbar spinal stenosis treatments and the biomechanical effects of spinal position, range of motion, and the use of interspinous process spacers. Method: Method EMBASE and PubMed were searched to find studies reporting on the safety and performance of nonsurgical treatment, including physical therapy and pharmacological treatment, and surgical treatment, including direct and indirect lumbar decompression treatment. Results were supplemented with manual searches to include studies reporting on the use of interspinous process spacers and the review of biomechanical testing performed on the Superion device. Results: Results The effects of spinal position in extension and flexion have been shown to have an impact in the variation in dimensions of the spinal canal and foramina areas. Overall studies have shown that spinal positions from flexion to extension reduce the spinal canal and foramina dimensions and increase ligamentum flavum thickness. Biomechanical test data have shown that the Superion device resists extension and reduces angular movement at the implantation level and provides significant segmental stability. Conclusions: Conclusions Superion interspinous lumbar decompression is a minimally invasive, low-risk procedure for the treatment of lumbar spinal stenosis, which has been shown to have a low safety profile by maintaining sagittal alignment, limiting the potential for device dislodgment or migration, and to preserve mobility and structural elements.